Uma janela tropical: análise do desempenho luminoso de ambientes com aberturas sombreadas para o clima de Natal/RN - Araújo, Juliana de Sá (2012)
This master thesis introduces assessment procedures of daylighting performance in office rooms with shaded opening, recommendations for Natal-RN (Latitude 05,47' S, Longitude 35,11' W). The studies assume the need of window exterior shading in hot and humid climate buildings. The daylighting performance analyses are based on simulated results for three levels of illuminance (300,500 e 1000 lux) between 08h00 e 16h00, in rooms with 2,80 m height, 6 m large and 4 m, 6 m e 8 m depths, with a centered single opening, window wall ratio (20%, 40% e 60%), four orientations (North, East, South and West), and two types of sky (clear and partially cloudy). The sky characteristics were statistically determined based on hourly data from INPE-CRN solar and daylighting weather station. The lighting performance is resulted from dynamic computer simulation of 72 models using Troplux 3.12. The simulation results were assessed using a new parameter to quantify the use of interior daylighting, the useful percentage of daylight (PULN), which corresponds to the time fraction with satisfactory light, in accordance with the illuminance design. The passive zone depths are defined based on the PULN. Despite the failures of illuminance data from the weather station, the analyses ratified the high potential of daylighting for shaded rooms. The most influential variables on the lighting performance are the opening size and the illuminance of design, while the orientation is a little influential